Implementation of Risk-Based Thinking ISO 9001:2015 Using FMEA in the Manufacturing Industry: A Case Study of PT XYZ - Rahmawati, Dwitya Nur; Suryadi, Edi; Hadijah, Hady Siti; Rasto, Rasto (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Risk-Based Thinking (RBT) is a foundational principle in ISO 9001:2015; however, many manufacturing companies continue to face challenges in translating this abstract concept into concrete, measurable operational actions. This study aims to develop and validate a practical framework for implementing RBT through Failure Mode and Effect Analysis (FMEA) within the quality management system of a manufacturing environment. A mixed-method case study was conducted at PT XYZ, a manufacturing company in Indonesia. The FMEA implementation included identifying failure modes, assessing severity-occurrence-detection, and calculating Risk Priority Numbers (RPN). Data collection encompassed stakeholder interviews, document analysis, and performance monitoring over a 24-month period. The FMEA process successfully identified 23 significant risks, categorized as critical (5 risks), high (8 risks), medium (7 risks), and low (3 risks). Post-implementation analysis revealed an average RPN reduction of 58%, from a range of 392–504 to 113–168, an increase in ISO 9001:2015 compliance from 83.8% to 96%, and notable improvements in operational performance. FMEA proves to be an effective pathway for operationalizing RBT within the ISO 9001:2015 framework in manufacturing contexts. The validated framework offers a practical guideline for the systematic implementation of risk management, contributing to enhanced quality management effectiveness and organizational competitiveness.